MODEL LEMBAGA KEUANGAN MIKRO (LKM) UNTUK MENGELOLA KEUANGAN MASYARAKAT (Studi di Kabupaten Jepara dan Karanganyar) - Wiwin Widiastuti; Sriyanto Sriyanto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2013)
The objective of the research was to identify micro finance institution model which is fit with the needs of low income community and community which has business within cluster. The research was conducted in Karanganyar dan Jepara regency. The result showed that not all of the government funding that goes to community were sustained. The sustained and effective integrated microfinance model was the one which has empowerment orientation, in the form of village corporation and microfinance model which has bussiness within cluster orientation, in form of “koperasi”